THE INFLUENCE OF ADVANCED MATERNAL AGE ON PREGNANCY COURSE AND OUTCOME IN PATIENTS WITH GLUCOSE METABOLISM DISORDERS IN PREGNANCY - Khusain, Arailym (Nazarbayev University School of Medicine, 2024)
The prevalence of pregnancies in women of advanced age, which is defined to be over 35 years, has increased globally, raising concerns about associated risks such as hypertension, gestational diabetes (GD), preeclampsia, miscarriage and preterm birth. Even though these risks are widely recognized, the impact of advanced age on the course and outcome of pregnancy among women with glucose metabolism disorders (GMDs) is still underexplored. This study aims to examine the specific impact of advanced maternal age on pregnancy courses and outcomes in women with GMDs. The clinical records of women with GMDs who gave birth between 2013 and 2017 where retrospectively analyzed. 281 women were divided into three groups by age: <35, 35- 40 and >40 years old. According to the study results, there is a significant association between advanced maternal age and higher body mass index (BMI), blood pressure (BP) and pre-pregnancy hypertension in patients with GMDs. Interestingly, fasting glucose levels were lower with gestational diabetes diagnosed at earlier gestational ages as maternal age increased. Among the neonatal outcomes, the analysis showed significantly higher incidence of neonatal hypoglycemia with advancing maternal age, and the frequency of macrosomia was also higher among these patients. Therefore, early screening and targeted monitoring of women of advanced age with GMDs is highly recommended to mitigate these risks. Further research is needed to develop comprehensive management strategies for this high-risk population and to develop a pre-pregnancy program focused on dietary and lifestyle modifications to improve the pregnancy outcomes in advanced age pregnancies with GMDs.
Keywords: type of access: gated access; pregnancy; metabolism disorders